ANALISIS SPASIAL POTENSI AIR TANAH DI KABUPATEN WAJO PROVINSI SULAWESI SELATAN - Badwi, Nasiah (UNIVERSITAS NEGERI MAKASSAR, 2024)
ABSTRACTWater is a very important necessity in life. The need for water is increasing and growing, because the population continues to grow. The purpose of this study illustrates the potential of groundwater in Wajo Regency. The analysis methods used are: Remote Sensing and Geographic Information Systems. There are 7 variables that are stacked in this study, namely: Rainfall, Rock Type, Soil Type, Place Altitude, Slope Slope, Vegetation Density and Land Use. The results showed that there are three classes of groundwater potential, namely: low, medium, and high. The largest area is in the medium class covering an area of 213,017 Ha (90.02 percent) spread across all districts in the Wajo Regency area. High groundwater potential class covering an area of 418,464.8 Ha (7.80 percent) spread across 8 districts, namely: Pitumpanua, Keera, Sajoangin, Penrang, Takkalalla, Bola, Belawa, and Maniangpajo. The dominant factors as determinants of high and low groundwater potential in Wajo Regency are the 7 variables that are mutually combined between variables but the most dominant are: Rainfall, Rock Type, Soil Type, and Land Use. The groundwater potential class is now in the medium class. These conditions must be maintained to prevent a groundwater crisis in Wajo Regency